2014
DOI: 10.1039/c4sm00415a
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous worm gels can be reconstituted from freeze-dried diblock copolymer powder

Abstract: Worm-like diblock copolymer nanoparticles comprising poly(glycerol monomethacrylate) (PGMA) as a stabilizer block and poly(2-hydroxypropyl methacrylate) (PHPMA) as a core-forming block were readily synthesized at 10% w/w solids via aqueous dispersion polymerization at 70 °C using Reversible Addition-Fragmentation chain Transfer (RAFT) chemistry. On cooling to 20 °C, soft transparent free-standing gels are formed due to multiple inter-worm interactions. These aqueous PGMA-PHPMA diblock copolymer worms were free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 59 publications
4
57
0
Order By: Relevance
“…[75] Free-standing gels could be reconstituted after freeze-drying by re-dissolving in water at 3-5 °C prior to heating to room temperature. [76] The (de)gelation temperature of p(GMA x -b-HPMA y ), below room temperature in the above cases, could be increased to 31 °C by the incorporation of 30 mol-% of hydrophilic di(ethylene glycol) methyl ether methacrylate (DEGMA) co-monomers into the core-forming block. Upon cooling from above 31 °C to 5 °C, the worm particles reversibly disintegrated into weakly interacting copolymer chains with an average aggregation number of ≈4.…”
Section: Temperature Responsiveness In Aqueous Dispersionmentioning
confidence: 98%
See 1 more Smart Citation
“…[75] Free-standing gels could be reconstituted after freeze-drying by re-dissolving in water at 3-5 °C prior to heating to room temperature. [76] The (de)gelation temperature of p(GMA x -b-HPMA y ), below room temperature in the above cases, could be increased to 31 °C by the incorporation of 30 mol-% of hydrophilic di(ethylene glycol) methyl ether methacrylate (DEGMA) co-monomers into the core-forming block. Upon cooling from above 31 °C to 5 °C, the worm particles reversibly disintegrated into weakly interacting copolymer chains with an average aggregation number of ≈4.…”
Section: Temperature Responsiveness In Aqueous Dispersionmentioning
confidence: 98%
“…In this and subsequent studies, the p(GMA x ‐ b ‐HPMA y ) system and its thermoresponsiveness were investigated in detail including through electron microscopy, dynamic light scattering, variable temperature 1 H NMR measurements, SAXS, rheology, and fluorescence correlation spectroscopy . Free‐standing gels could be reconstituted after freeze‐drying by re‐dissolving in water at 3–5 °C prior to heating to room temperature . The (de)gelation temperature of p(GMA x ‐ b ‐HPMA y ), below room temperature in the above cases, could be increased to 31 °C by the incorporation of 30 mol‐% of hydrophilic di(ethylene glycol) methyl ether methacrylate (DEGMA) co‐monomers into the core‐forming block.…”
Section: Temperature‐responsive Dispersion Pisa Nano‐objectsmentioning
confidence: 99%
“…Similar patterns, albeit at even lower temperatures, have been recently reported for an aqueous dispersion of a PGMA57-PHPMA140 diblock copolymer. 39 This is reasonable, since incorporation of the relatively hydrophilic DEGMA comonomer should favor molecular dissolution.…”
Section: Saxs Studiesmentioning
confidence: 99%
“…This is consistent with smallangle X-ray scattering (SAXS) studies recently reported for closely related PGMA 57 -block -PHPMA 140 in methanol. [ 37 ] Thus, the steady increase in diffusion coeffi cient that is observed in Figure 3 below the worm-to-sphere transition is consistent with the partial dissociation of the spheres to form near-molecularly dissolved copolymer chains at suffi ciently low temperatures. [ 37 ] However, the temperature at which this order-disorder transition occurs is not reached in the current study, with the smallest radius observed being 8 ± 4 nm at 5 °C.…”
Section: Resultsmentioning
confidence: 51%
“…Experiments investigating the thermoresponsive behavior of these rhodamine-labeled PGMA-PHPMA diblock copolymer nanoparticles were performed at pH 3.9; the copolymer was freeze-dried after its synthesis and then reconstituted using ice-cold water at this initial pH. [ 37 ] All FCS data were acquired using an inverted LSM510 Meta confocal microscope equipped with a ConFocor2 FCS module. The setup was calibrated using free RhB dye in order to allow optimization of the pinhole dimensions, placement, and fi lters.…”
Section: Methodsmentioning
confidence: 99%